Synthesis and Evaluation of HKHK-PKKKRKV and Its Lipopeptide as New Gene Delivery Candidates - Muthia, Nurul; Hidayat, Ace Tatang; Tarwadi, Tarwadi; Maharani, Rani (Trends in Sciences, 2025)
A major challenge in the delivery of genetic material is finding safe and effective vectors to deliver genetic material into target cells. Although virus-based vectors have proven to be effective in delivering genes to the cell nucleus, they often turn out to be harmful and interact with host cells. On the other hand, naturally available or chemically synthesized nonviral vectors are relatively safer but have low delivery efficiency. Research regarding the use of lipopeptide-based compounds as non-viral vectors for the delivery of genetic material is still limited. This study aims to synthesize NLS-based peptide, HKHK-PKKKRKV (P) and its lipopeptide, C16-HKHK-PKKKRKV (LP), and to evaluate their capability to transport genetic material into the nucleus in vitro. Synthesis of peptide and its lipopeptide was performed using the solid-phase method on 2-chlorotrityl chloride resin with Fmoc chemistry. HATU/HOAt was used as coupling reagents for amide bond formation between 2 amino acids, and DIC/Oxyma was used for fatty acid conjugation to the peptidyl resin. The yields of peptide and lipopeptide obtained were 33 and 26.4 %, respectively. Their structures were confirmed by ESI-TOF-MS, 1H-NMR, and 13C-NMR. The physicochemical analysis of peptide and lipopeptide showed that they were capable of condensing and protecting DNA from enzyme degradation at a ratio of 1:8 to DNA. The peptide and lipopeptide were found to be less efficient for transfection in HEK-293T cells because they required a high concentration (16,000 ng/μL). Nonetheless, peptide and lipopeptide concentrations of 250 - 16,000 ng/μL showed no toxicity to the cells. HIGHLIGHTS Successful synthesis of NLS-based peptide, HKHK-PKKKRKV, and its amphiphilic lipopeptide C16-HKHK-PKKKRKV using solid-phase method on 2-chlrotrityl resin with Fmoc chemistry. Implementation of efficient synthesis lipopeptide techniques, which overcame difficult aggregation and hydrophobic interaction issues throughout the assembly process. Demonstration of the lipopeptide’s capability as a versatile non-viral vector for gene delivery with adaptable properties for nuclear localization, cellular entrance, and nucleic acid binding. GRAPHICAL ABSTRACT